Preparations underway for the seafood festival - Mumbai Archive Project Team (Jio Institute, 2024)
Teams are formed, and preparations start at least a week before the festival. Around 50–60 stalls are set up at the Versova Koli Seafood Festival. To run their stall, each woman in the group chips in with individual contributions. They use this combined fund to buy fish stock and cooking ingredients and pay the organizing committee for décor, rent, and electricity.